CLINICAL PHARMACOLOGICAL APPROACH TO THE USE OF ANTIARRHYTHMIC DRUGS (Multidisciplinary Journal of Science and Technology, 2025)
The clinical pharmacology of antiarrhythmic drugs occupies a central position in cardiovascular medicine, representing one of the most intricate and demanding fields due to the narrow therapeutic margins and potential proarrhythmic risks of these agents. Antiarrhythmic therapy aims to restore and maintain normal cardiac rhythm, prevent recurrent arrhythmias, and reduce morbidity and mortality associated with cardiac dysrhythmias. This article explores the pharmacodynamics, pharmacokinetics, clinical applications, and safety considerations of antiarrhythmic drugs, emphasizing individualized therapy based on electrophysiological mechanisms, patient comorbidities, and risk stratification. The discussion integrates the classical Vaughan Williams classification with modern receptor-based and electrophysiological insights, offering a comprehensive understanding of the rational use of these potent yet potentially hazardous agents.